Happiness : the science behind your smile - Nettle, Daniel (OUP E-Books., 2005)
In a world obsessed by happiness, this is the first book to look thoroughly at what happiness is and how it works. Bringing together insights from psychiatry, psychology, and philosophy, psychologist Nettle examines whether people are basically happy or unhappy, whether success can make us happy, what sort of remedies to unhappiness work, why some people are happier than others, and much more. We discover the evolutionary reason why negative thoughts are more powerful than positive ones. We read that happiness varies from country to country--the Swiss are much more happy than Bulgarians. Nettle discusses the brain systems underlying emotions and moods, ranging from serotonin, "the happiness chemical"; to mood enhancing drugs such as D-fenfluramine, which reduces negative thinking in less than an hour; to the part of the brain that, when electrically stimulated, provides feeling of benevolent calm and even euphoria.--From publisher description